A tunable quasi-zero stiffness isolator based on a linear electromagnetic spring. (15th September 2020) - Yuan, Shujin; Sun, Yi; Zhao, Jinglei; Meng, Kai; Wang, Min; Pu, Huayan; Peng, Yan; Luo, Jun; Xie, Shaorong
Abstract: High-static-low-dynamic stiffness (HSLDS) or quasi-zero stiffness (QZS) has attracted a great deal of attention in vibration isolation research. However, most existing HSLDS isolators have a nonlinear stiffness, which may lead to nonlinear behavior under a large excitation. To improve the isolation performance under violent vibration conditions, a tunable QZS isolator with a long working stroke is proposed in this paper. The isolator is developed by combining a linear electromagnetic spring (LES) in parallel with a conventional linear isolation system. The LES contains three toroidal coils arranged coaxially with a ring magnet. By controlling the current excited to the coils, the LES can generate a linear negative stiffness that balances the positive stiffness of the conventional system, thereby achieving a quasi-zero stiffness over the long stroke. The influence of the LES parameters on its stiffness is studied using the derived stiffness analysis model, and based on the results, a design procedure to increase the tunable stiffness range and extend the linear stroke is proposed. The dynamic response of the isolator is analyzed and experimentally verified. Finally, it turns out that the QZS isolator is suitable for large excitations and can be tuned online. Highlights: Quasi-zero stiffness isolator with a long working stroke and suitable for violent vibration. Increased isolation performance through online tunable negative stiffness. Design procedure for the electromagnetic spring to enlarge tunable range and linear stroke. Modeling and testing of the tunable Quasi-zero stiffness isolator to verify the performance.